The Impact of ESL Discussion Groups in an Undergraduate Counselling Psychology Course - Dwyer, Sonya Corbin (International Dialogues on Education Journal, 2020)
This study aimed to understand the impact of an experiential learning activity in a third year undergraduate course on the theory and practice of counselling and psychotherapy at a small Canadian university campus. The experiential learning activity required students to participate in bi-weekly one-to-one discussion groups with international students participating in English as a Second Language (ESL) programs at the university. The results of two pre- and post-assessment measures demonstrated that the students’ cultural competence and cultural intelligence scores improved after participating in the course. Findings may encourage more university educators to develop experiential learning activities between domestic and international students.